Long-Term Outcomes After Implantation of Magnesium-Based Bioresorbable Scaffolds—Insights From an All-Comer Registry - Bossard, Matthias; Madanchi, Mehdi; Avdijaj, Dardan; Attinger-Toller, Adrian; Cioffi, Giacomo Maria; Seiler, Thomas; Tersalvi, Gregorio; Kobza, Richard; Schüpfer, Guido; Cuculi, Florim (Frontiers in Cardiovascular Medicine, 2022)
Background: The magnesium-based, sirolimus-eluting bioresorbable scaffold Magmaris™ (Mg-BRS) showed promising clinical outcomes, including low rates of both target lesion failure (TLF) and scaffold thrombosis (ScT), in selected study patients. However, insights regarding long-term outcomes (>2 years) in all-comer populations remain scarce. Methods: We analyzed data from a single-center registry, including patients with acute (ACS) and chronic coronary syndrome (CCS), who had undergone PCI using Mg-BRS. The primary outcome comprised the device-oriented composite endpoint (DoCE) representing a hierarchical composite of cardiac death, scaffold thrombosis (ScT), target vessel myocardial infarction (TV-MI) and clinically driven target lesion revascularization (TLR) up to 5 years. Results: In total, 84 patients (mean age 62±11 years and 63 (75%) males) were treated with Mg-BRS devices between June 2016 and March 2017. Overall, 101 lesions had successfully been treated with Mg-BRS devices using 1.2±0.4 devices per lesion. Pre- and post-dilatation using dedicated devices had been performed in 101 (100%) and 98 (97%) of all cases, respectively. After a median follow-up time of 62 (61-64) months, 14 (18%) patients had experienced DoCE’s, whereas ScT was encountered in 4 (4.9%) patients (early ScTs (<30 days) in 3 cases, 2 fatal cases). In 4 (29%) of DoCE cases, optical coherence tomography confirmed Mg-BRS collapse and uncontrolled dismantling. Conclusions: In contradiction to earlier studies, we encountered a relatively high rate of DoCE’s in an all-comer cohort treated with the Mg-BRS. We even observed scaffold collapse and uncontrolled dismantling. This implicates that this metal-based BRS requires further investigation and may only be used in highly selected cases.